Social-ecological resilience of small-scale coffee production in the Porce river basin, Antioquia (Colombia) (2018)
ABSTRACT : This research was carried out in the Porce river basin, Antioquia (Colombia) with nine coffee growing families in charge of conventional systems and in transition to the organic production of coffee. The farms were characterized from an agroecological perspective, while evaluating the social, economic and technical-productive dimensions. It was detected that the two main threats faced by small farmers in this area are climatic variability and fluctuations in coffee prices. Using the RIH Risk Index methodology, a set of indicators was proposed to reflect the vulnerability and the response capacity of these families.